2007
DOI: 10.1089/ars.2007.9.219
|View full text |Cite
|
Sign up to set email alerts
|

H2O2Signaling in the Nigrostriatal Dopamine Pathway Via ATP-Sensitive Potassium Channels: Issues and Answers

Abstract: The role of reactive oxygen species (ROS) as signaling agents is increasingly appreciated. Studies of ROS functions in the central nervous system, however, are only in their infancy. Using fast-scan cyclic voltammetry and fluorescence imaging in brain slices, the authors discovered that hydrogen peroxide (H2O2) is an endogenous regulator of dopamine release in the dorsal striatum. Given the key role of dopamine in motor, reward, and cognitive pathways, regulation by H2O2 has implications for normal dopamine fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 141 publications
(208 reference statements)
0
32
0
Order By: Relevance
“…In this study, we also showed that palmitate induced apoptosis through ROS generation in HUVECs. Despite recent studies concerning the role of ROS as a signaling molecule (Avshalumov et al 2007), the imbalance between detoxifying antioxidant system and ROS generation leads to divergent pathological disorders (Stocker & Keaney 2004, Schulze & Lee 2005, Takimoto & Kass 2007. Accumulating evidence also indicates that ROS mediates endothelial cell apoptosis to many different stresses such as bacterial toxin, cytokine, and neuronal hormone (Deshpande et al 2000, Suematsu et al 2002, Sylte et al 2004, Kuckleburg et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also showed that palmitate induced apoptosis through ROS generation in HUVECs. Despite recent studies concerning the role of ROS as a signaling molecule (Avshalumov et al 2007), the imbalance between detoxifying antioxidant system and ROS generation leads to divergent pathological disorders (Stocker & Keaney 2004, Schulze & Lee 2005, Takimoto & Kass 2007. Accumulating evidence also indicates that ROS mediates endothelial cell apoptosis to many different stresses such as bacterial toxin, cytokine, and neuronal hormone (Deshpande et al 2000, Suematsu et al 2002, Sylte et al 2004, Kuckleburg et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations of the protection mechanism of mitochondrial K + channel suggest that the opening of mito-K ATP induced by increasing reactive oxygen species (ROS) production combines with blunting mitochondrial Ca 2+ accumulation, which finally improves the mitochondrial energy production [20] . As hydrogen peroxide (H 2 O 2 ) generate in all cells by mitochondrial respiration, Avshalumov MV examined regulation of K ATP channels in nigral dopaminergic neurons to certain the relationship between H 2 O 2 with mito-K ATP channels [21][22] . The observation confirms an essential role of H 2 O 2 in activating K ATP channels.…”
Section: Roles Of K Atp Channels In Pdmentioning
confidence: 99%
“…In addition, other intracellular factors like phosphoinositol phosphates (e.g. PIP2), G proteins, or protein kinases could modulate the metabolic sensitivity of K ATP channels as well [13,22] . One has to be highlighted is that the regulation of cell activity by H 2 O 2 and metabolic sensitivity of mito-K ATP channels is mainly determined by the alternative expression of SUR subunits.…”
Section: Roles Of K Atp Channels In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DCF fluorescence imaging is not suitable for quantitative evaluation of absolute H 2 O 2 concentration, this dye can be used to monitor relative differences in basal and stimulated levels of H 2 O 2 . 19,44 Despite the fact that MSNs are electrically silent in brain slices, basal DCF fluorescence is detected in all cells tested, presumably reflecting tonic H 2 O 2 production through mitochondrial respiration required to maintain ion gradients. 22 During local electrical stimulation of dorsal striatum in ex vivo brain slices, each pulse of a stimulus train (e.g., 30 pulses, 10 Hz) elicits a single action potential in recorded MSNs ( Figure 2B); these spikes are AMPAR-dependent, as discussed further below.…”
mentioning
confidence: 96%